2012
DOI: 10.1186/1745-6673-7-22
|View full text |Cite
|
Sign up to set email alerts
|

Physical capacity and psychological mood in association with self-reported work ability in vibration-exposed patients with hand symptoms

Abstract: BackgroundThe aim of this study was to investigate whether self-reports of work ability correlated to the results of quantitative tests measuring physical capacity and a questionnaire assessing psychological mood in vibration-exposed patients with hand symptoms.MethodsThe participants comprised 47 patients (36 men and eleven women) with exposure to hand vibration and vascular and/or neurological symptoms in the hands. They performed several quantitative tests (manual dexterity, hand grip strength, finger stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 22 publications
2
21
0
1
Order By: Relevance
“…Our findings of Bovenzi et al an increased risk for reduced work ability in the HTVexposed workers may be of help for the implementation of further studies aimed at investigating the impairment to work capacity caused by long-term exposure to vibration (25). These adverse effects, however, may not be attributed only to vibration since working with vibratory tools entails also exposure to ergonomic risk factors such as hand/forearm physical overload which was associated with sensory symptoms, interference with work activities and limited work performance in this study.…”
Section: Exposure-response Relationship For Vibration-induced Sensorysupporting
confidence: 52%
“…Our findings of Bovenzi et al an increased risk for reduced work ability in the HTVexposed workers may be of help for the implementation of further studies aimed at investigating the impairment to work capacity caused by long-term exposure to vibration (25). These adverse effects, however, may not be attributed only to vibration since working with vibratory tools entails also exposure to ergonomic risk factors such as hand/forearm physical overload which was associated with sensory symptoms, interference with work activities and limited work performance in this study.…”
Section: Exposure-response Relationship For Vibration-induced Sensorysupporting
confidence: 52%
“…Other explanations such as additional effects from psychological mechanisms may also be plausible (16). It is further possible that workers with high exposure are more aware of signals and symptoms from their hands because they know that vibrations are potentially harmful.…”
Section: Edlund Et Almentioning
confidence: 99%
“…Other factors must also be considered however. In a previous study, we found that psychological status, assessed by the Hospital and Anxiety Depression Scale, had a considerable impact on work ability [ 9 ]. Thus a multidimensional approach, including psychological factors, is needed when studying work ability in vibration-exposed workers.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous investigation, the influence of psychological status on work ability in vibration-exposed workers was studied, using the Hospital Anxiety and Depression Scale [ 9 ]. This study of vibration-exposed workers with varying stages of vibration-induced neuropathy aimed to investigate the impact of factors that may affect work ability, e.g.…”
Section: Introductionmentioning
confidence: 99%